Operational Challenges of Low Power Hydro Plants - Atputharajah, Arulampalam (University of Jaffna, 2011)
This chapter discusses the electrical circuits and operations of low power hydro plants. Mainly small hydro and micro hydro power plants are covered. Both the grid connected and islanded operations are summarized. Grid connection issues and power quality problems are explained with some examples. Especially in the case of small hydro power plants, operational problems and solutions through strengthening its grid connection codes are enlightened. Finally in the case of micro hydro power plants, their electrical circuits are illustrated in details. Circuits used to obtain single phase output from a three-phase machine with machine optimized operation, electronic load controllers to maintain voltage and frequency are discussed.